The association of KRAS mutation with primary tumor location and survival in patients undergoing resection of colorectal cancers and synchronous liver metastases - Allievi, Niccolo; Goffredo, Paolo; Utria, Alan F.; Pisano, Michele; Poiasina, Elia; Lucianetti, Alessandro; Zhou, Paige; Hassan, Imran (Chinese Clinical Oncology; Vol 8, No 5 (October 09, 2019): Chinese Clinical Oncology (Molecular Markers in Colorectal Cancer), 2019)
Background: Recent evidence suggests that a mutation in the KRAS gene has a significant impact on the clinical behavior and prognosis of patients with metastatic colorectal cancer. The KRAS mutation (m-KRAS) has been associated with decreased survival among patient undergoing treatment with a curative and palliative intent. This is believed to be secondary to a reduced response to anti-EGFR chemotherapy agents and a more intrinsically aggressive biology. The aims of this study were to identify risk factors for m-KRAS in patients with curatively resected colorectal cancer and synchronous liver metastases and to assess its association with disease-specific survival (DSS). Methods: The Surveillance, Epidemiology and End Results (SEER) Database was surveyed for patients undergoing resection of colorectal cancer and synchronous liver metastases from 2010 to 2015. Results: A total of 806 patients were included, of which 40% hadm-KRAS. Right-sided primary lesions (OR 2.56, 95% CI: 1.90–3.44, P